Treasury Diagnostic Toolkit - Hashim, Ali (Washington, DC: World Bank, 2013)
Improvement in the management of public finances in developing countries has been an increasingly important focus of World Bank and IMF assistance to member countries. A key element in such assistance is the development of effective treasury systems. Treasury systems form the backbone for recording and processing all financial transactions related to the budget for any level of government. An integrated treasury system offers several significant benefits in managing public monies more effectively, including, greater financial control, improved monitoring of the governments cash position, and better planning of future requirements, better fiscal reporting, and availability of better data for budget formulation. The establishment of an effective treasury system will also contribute directly to improving the transparency and accountability of government. (b) Costing Model: Information system features obtained as a result of completing the detailed Treasury Systems Questionnaire described in Chapter 1 can be linked in to a simple costing model (described in Chapter 2) to generate first stage estimates of the likely cost of a comprehensive investment program. Chapter 2 sets out a costing for a typical program for illustrative purposes only, although the model has now been used in actual program development in several countries as the base for project development. (c) Application Software Questionnaire: Chapter 3 of this paper is intended to assist Treasury managers in the process of selecting appropriate application software from the wide range of options that are now available in the market. This part of the questionnaire focuses on Treasury specific requirements that are not commonly found in a statement of requirements for commercial accounting systems. It is intended to provide Treasury managers in client countries a benchmark to determine the goodness of fit of the major products on the market with the core Treasury functional processes and requirements.